Forensic Analysis From Death to Justice - Suresh Kumar Shetty, B.; Rao Padubidri, Jagadish (IntechOpen, 2016)
It is my pleasure to place before you the book ''Forensic Analysis - From Death to Justice'' which presents one of the major portions of the broad specialty of Forensic Science comprising mainly of Thanatology and Criminalistics. This book has been designed to incorporate a wide range of new ideas and unique works from all authors from topics like Forensic Engineering, Forensic Entomology and Crime Scene Investigation. I hope that it will be useful to practitioners of forensic medicine, experts, pathologists, law makers, investigating authorities, undergraduate and postgraduate medical school graduates of medicine.